Risk Aversion and Entrepreneurship: New Evidence Exploiting Exposure to Massive Earthquakes in Italy - Guido De Blasio; Maria De Paola; Samuele Poy; Vincenzo Scoppa (Institute of Labor Economics (IZA), 2018)
This paper investigates the impact of risk attitudes on the decision to become an entrepreneur. In contrast to previous research, we handle endogeneity issues relying on an instrumental variables strategy considering as a source of exogenous variation in risk aversion the early exposure to a massive earthquake. Using several waves of the Bank of Italy Survey of Household Income and Wealth (SHIW), we find that individuals experiencing an earthquake become significantly more risk averse. Second-stage estimates show that risk aversion has a significant negative impact on the probability of becoming an entrepreneur.
Keywords: D81; D91; L26; C36; 330; entrepreneurship; risk attitudes; natural disasters; instrumental variables